Anisotropy in creep properties of DS200 + Hf alloy. (28th June 2016) - Mataveli Suave, L.; Cormier, J.; Villechaise, P.; Bertheau, D.; Benoit, G.; Cailletaud, G.; Marcin, L.
Abstract : The directionally solidified Ni-based superalloy DS200 + Hf is used in aero-engines and industrial gas turbines for the manufacturing of intermediate and low-pressure turbine blades. This material consists of <0 0 1> columnar grains oriented along the solidification direction and with random secondary orientations. In this study, the creep behaviour of the DS200 + Hf alloy has been investigated along longitudinal and transverse directions. The main objective was to investigate the durability of this alloy and the damage mechanisms for four different crystalline microstructures: DS200 + Hf composed of fine grains loaded longitudinally, the same alloy composed of coarse grains or fine grains, loaded transversally to the solidification direction and finally, the single crystal version, Mar-M200 + Hf, loaded along a <0 0 1> crystallographic orientation. Creep tests were performed from 750°C up to 1100°C. Under all conditions, a pronounced decrease in the strain to failure is observed for specimens loaded along the transverse direction compared to specimens tested along longitudinal direction or single crystals. Fracture surface observations revealed that the lower creep ductility along such a loading direction results from an intergranular failure mode. Furthermore, the creep life anisotropy significantly decreases when temperature increases. Additional creep experiments under vacuum at 900°C and experiments using single crystalline specimens far away from the <0 0 1> crystallographic orientation show a prominent damaging role of oxidation at very high temperature and a major contribution of the local crystallography at low temperatures. In addition, the grain size effect observed when testing in the transverse direction only results from the grain boundary oxidation.